1979
DOI: 10.1002/jez.1402070103
|View full text |Cite
|
Sign up to set email alerts
|

A sex pheromone secreting gland in the terrestrial snail, Euhadra peliomphala

Abstract: The head-wart found in the snail, Euhadra peliomphala, consists of a number of elevated dermal tubercles covered by a particularly thick epithelium. The head-wart and its epithelial cells attain full size by rapid growth at the time of sexual maturation. When two snails meet in the breeding season, their head-warts become conspicuously protuded. After touching the partner's head-wart with large tentacles, each becomes excited, protrudes its penial mass, and finally copulates. Protrusion of the head-wart and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Audition is absent, and the eye is incapable of image formation. Olfaction therefore serves important behavioral functions in food finding (Croll and Chase, 1980), localization of conspecifics (Chase et al, 1978;Takeda and Tsuruoka, 1979), and homing (Gelperin, 1974;Lind, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Audition is absent, and the eye is incapable of image formation. Olfaction therefore serves important behavioral functions in food finding (Croll and Chase, 1980), localization of conspecifics (Chase et al, 1978;Takeda and Tsuruoka, 1979), and homing (Gelperin, 1974;Lind, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear which cues snails use to discriminate the mating status of their mates. However, chemosensory cues may play an important role in this discrimination, because it is reported that snails of E. peliomphala , a species that is closely related to E. quaesita , communicate with air-borne chemicals [ 50 ]. Body contact during courtship may also provide an opportunity to communicate and discriminate mating status.…”
Section: Discussionmentioning
confidence: 99%
“…1). The protruded tissues are the so-called head wart (Taki, 1930(Taki, , 1935 and are considered to release a sex pheromone (Takeda and Tsuruoka, 1979). The sexually aroused snails exhibit the protruded head wart before and during courtship behaviour in camaenid species, including the study species (e.g.…”
Section: Materials and Methods Study Speciesmentioning
confidence: 99%